1993
DOI: 10.1159/000116920
|View full text |Cite
|
Sign up to set email alerts
|

Protein Analysis in Cerebrospinal Fluid

Abstract: To examine the possible influence of the blood-CSF barrier function on mathematical formulas for estimating intrathecal IgG production {IgG index, Tourtellotte’s formula [TOURT], Schuller and Sagar’s formula [Schull], and Reiber and Felgenhauer’s formula [IgG(loc)]}, we analysed serum and CSF samples from 105 healthy individuals, aged 18-88 years, and 816 consecutive patients without oligoclonal IgG bands (OCBs) in the CSF, aged 18-91 years. In healthy individuals there was no significant correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…102 In fact, many human studies have revealed increased BBB permeability for elderly, healthy subjects compared with young, healthy subjects. 103,104 Changes also occur during aging at the level of endothelial cells such as a decreased number of endothelial cell mitochondria, impaired endothelium dependent vasodilation, and a loss of elongation in endothelial cells. 45,105107 The mechanisms proposed to be involved in age-related BBB breakdown include increased oxidative stress, 108 inflammation and hypertension.…”
Section: High-fat Diets and Cognitionmentioning
confidence: 99%
“…102 In fact, many human studies have revealed increased BBB permeability for elderly, healthy subjects compared with young, healthy subjects. 103,104 Changes also occur during aging at the level of endothelial cells such as a decreased number of endothelial cell mitochondria, impaired endothelium dependent vasodilation, and a loss of elongation in endothelial cells. 45,105107 The mechanisms proposed to be involved in age-related BBB breakdown include increased oxidative stress, 108 inflammation and hypertension.…”
Section: High-fat Diets and Cognitionmentioning
confidence: 99%